2022
DOI: 10.1002/bit.28222
|View full text |Cite
|
Sign up to set email alerts
|

Physiological metabolic topology analysis of Halomonas elongata DSM 2581T in response to sodium chloride stress

Abstract: The halophilic bacterium Halomonas elongata DSM 2581 T generally adapts well to high level of salinity by biosynthesizing ectoine, which functions as an important compatible solute protecting the cell against external salinity environment.Halophilic bacteria have specific metabolic activities under high-salt conditions and are gradually applied in various industries. The present study focuses on investigating the physiological and metabolic mechanism of H. elongata DSM 2581 T driven by the external salinity en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
(77 reference statements)
3
6
0
Order By: Relevance
“…Under 5% NaCl shock, H. elongata exhibited high robustness, quickly restoring its growth rate and ultimately achieving the highest biomass. This finding is consistent with the previous study indicating a maximum specific growth rate under 6% NaCl condition [19]. When exposed to 8% NaCl, H. elongata required a longer recovery time for the cell growth, while the ectoine content rapidly increased after shock and reached the highest level.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Under 5% NaCl shock, H. elongata exhibited high robustness, quickly restoring its growth rate and ultimately achieving the highest biomass. This finding is consistent with the previous study indicating a maximum specific growth rate under 6% NaCl condition [19]. When exposed to 8% NaCl, H. elongata required a longer recovery time for the cell growth, while the ectoine content rapidly increased after shock and reached the highest level.…”
Section: Discussionsupporting
confidence: 93%
“…When exposed to 8% NaCl, H. elongata required a longer recovery time for the cell growth, while the ectoine content rapidly increased after shock and reached the highest level. This finding is also consistent with previous research, where the highest ectoine production was observed under 8% NaCl condition [19]. Notably, the obtained maximum ectoine productivity (1450 ± 99 mg/L/h) in 8% NaCl shock was substantially higher than that in other halophiles and even exceeded its value (1130 ± 20 mg/L/h) under normal cultivation in 8% NaCl [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, under 100 mM NaCl, the yield of ectoine was significantly increased, reaching 98.9 mg/l. It has also been reported that ectoine production increased with the concentration of NaCl in the environment ( Ning et al, 2016 ; Yu et al, 2022 ), and this phenomenon also occurred in the synthesis of glucosylglycerol and sucrose ( Song et al, 2016 ; Cui et al, 2021 ). With the further increase of salt concentration, the yield of ectoine decreased compared with under 100 mM NaCl, most probably due to the worse growth caused by salt stress.…”
Section: Resultsmentioning
confidence: 91%